Sosialisasi dan Edukasi Pemanfaatan Limbah Kulit Pisang sebagai Masker Wajah Alami Kaya Antioksidan di Kecamatan Marpoyan Damai, Pekanbaru - Putri Ade Rahma Yulis; Yelfira Sari; Desti Desti (Jurnal Pengabdian Pada Masyarakat, 2019)
SOCIALIZATION AND EDUCATION ON THE UTILIZATION OF BANANA SKIN WASTE AS ANTIOXIDANT-RICH NATURAL FACE MASKS IN MARPOYAN DAMAI DISTRICT, PEKANBARU. The fact at this time is the increasing level of consumer consumption of beauty products. It does not only occur among adult women but also teenager. But the consumptive level not accompanied by purchasing power of quality products. Based on interviews with residents of the village of East Sidomulyo, most of the citizens are among adult women and teenagers that they mostly use ready-made masks that are sold in the market because it is more practical and faster in the process of use without considering the possibility of its contents which are harmful to skin health. The problem of the partners is to encourage service in the form of socialization and education to the local community to be able to take advantage of the banana peel waste that is widely available in the environment because it is now became popular a variety of processed banana products, but in terms of waste has not been utilized at all. This education is based on several studies that banana peels contain high antioxidants so it is very good if it can be processed as a mask for a facial skin care. In addition, the utilization of waste will be able to reduce pollution that might occur in the environment due to banana peels that are not treated. The existence of this activity was very welcomed by residents, this can be seen from the enthusiasm of residents asking questions regarding the problems presented and the impression of some residents who want this activity to be carried out continuously, so that more people feel the benefits and they are very enthusiastic to directly apply the knowledge.